Verification of German methane emission inventories and their recent changes based on atmospheric observations - Levin, Ingeborg; Glatzel Mattheier, Holger; Marik, Thomas; Cuntz, Matthias; Schmidt, Martina; Worthy, Douglas E (Journal of Geophysical Research: Atmospheres, 1999)
International audience Continuous methane concentration records and stable isotope observations measured in the suburbs of Heidelberg, Germany, are presented. While 13C-CH4 shows a significant trend of 0.14‰ per year, toward more depleted values, no trend is observed in the concentration data. Comparison of the Heidelberg records with clean air observations in the North Atlantic at Iza ̃na station (Tenerife) allows the determination of the continental methane excess at Heidelberg, decreasing by 20% from 190 ppb in 1992 to 150 ppb in 1997. The isotope ratio which is associated with this continental methane pileup in the Heidelberg catchment area shows a significant trend to more depleted values from 13Csource 47.4 1.2‰ in 1992 to 52.9 0.4‰ in 1995/1996, pointing to a significant change in the methane source mix. Total methane emissions in the Heidelberg catchment area are estimated using the 222radon (222Rn) tracer method: from the correlations of half-hourly 222Rn and CH4 mixing ratios from 1995 to 1997, and the mean 222Rn exhalation rate from typical soils in the Rhine valley, a mean methane flux of 0.24 0.5 g CH4 km 2 s 1 is derived. For the Heidelberg catchment area with an estimated radius of approximately 150 km, Core Inventories Air 1990 (CORINAIR90) emission estimates yield a flux of 0.47 g CH4 km 2 s 1, which is about 40% higher than the 222Rn-derived number if extrapolated to 1990. The discrepancy can be explained by overestimated emissions from waste management in the CORINAIR90 statistical assessment. The observed decrease in total emissions can be accounted for by decreasing contributions from fossil sources (mainly coal mining) and from cattle breeding. This finding is also supported by the observed decrease in mean source isotopic signatures.